Etiology and Clinical Features of Full-Term Neonatal Bacterial Meningitis: A Multicenter Retrospective Cohort Study - Xu, Min; Hu, Lan; Huang, Heyu; Wang, Liping; Tan, Jintong; Zhang, Yongjun; Chen, Chao; Zhang, Xi; Huang, Lisu (Frontiers in Pediatrics, 2019)
Objective: Neonatal bacterial meningitis is a severe infectious disease with a high risk of neurodevelopmental sequelae. The causative pathogens may be related to specific clinical features of the disease. Therefore, this study aimed at determining the pathogen-specific and clinical features of bacterial meningitis in full-term neonates. Methods: We enrolled neonates from the Shanghai Neonate Meningitis Cohort (2005-2017), which is a multicenter retrospective cohort that recruits almost all full-term neonates in Shanghai who underwent lumbar puncture. Patient history and clinical examination results were extracted from the computer-documented information systems of four hospitals. The trends of pathogen distribution were analyzed and differences in the clinical manifestations, treatment, and clinical outcomes at discharge were compared according to the causative pathogen. Logistic regression was used to evaluate the pathogen-specific risk of neurological complications. Results: In total, 518 cases of neonatal meningitis, including 189 proven cases, were included. Group B Streptococcus (GBS) and Escherichia coli (E. coli) were the leading pathogens in proven cases of early-onset and late-onset neonatal meningitis, respectively. The proportion of early-onset and late-onset GBS and late-onset E. coli meningitis cases increased gradually. GBS meningitis had the highest risk of neurological complications, whereas the overall incidence of hydrocephalus and brain abscess in E. coli was higher than that in GBS. Conclusions: Rates of neonatal GBS and E. coli meningitis were high in 2005-2017 in Shanghai, and the risk of neurological complications was also high. Therefore, active prevention, rational use of antibiotics, and continuous monitoring of GBS and E. coli in neonates should be initiated in Shanghai.